Tracking Wichita Falls' Path From DPR to IPR. Issue 2 (4th March 2021) - Nix, Daniel K.; Southard, Mark; Burris, Harold; Adams, Hunter; Schreiber, Russell
Abstract : The City of Wichita Falls, Texas, made international news in 2014 when its water system became a water reuse pioneer. In response to a historic drought, the city simultaneously planned and implemented direct potable reuse (DPR) and indirect potable reuse (IPR) systems to see it through the drought and respond to future water shortages. Now, the city is a role model for water utilities around the world.